MORPHOLOGICAL DIFFERENTIATION AND SPORT RESULTS OF MALE AND FEMALE WEIGHTLIFTERS - Saczuk, Jerzy; Wasiluk, Agnieszka (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose of this study was to analyze the types of body structure of elite Polish weightlifters of both genders, depending on their sports’ achievements. Material: Somatic measurements of weightlifters were fulfilled during individual Junior and Senior National Championships. Overall, a total of 127 male athletes (66 juniors and 61 seniors) were examined, along with 63 female athletes (32 juniors and 31 seniors). The levels of endomorphism, mesomorphism, and ectomorphism were determined and compared to the reference values of adolescents and young adults who did not engage in any sports discipline. The scores achieved during the National Championships were converted into Sinclair scale points, and each athlete was classified into one of three categories of sports outcome (superior, intermediate, or poor). Results: The athletes were characterized by higher level of endomorphism and mesomorphism and lower level of ectomorphism than non-training individuals. This suggests that the level of body adiposity is not considered during the qualification and selection of examined weightlifters. Male seniors were the only group with lower adiposity than the reference group. Analysis of body structure in relation to sports results revealed a tendency towards increased mesomorphism and decreased ectomorphism associated with higher level of skills and training experience in studied men and women. This reflects the appropriateness of the training process. However, not all differences between analyzed groups proved statistically significant. Conclusions: Training methods and diet should be verified to reduce adiposity in athletes as aside from male seniors, this parameter proved higher than in the respective reference groups, and there was no tendency towards a decrease in this parameter in concert with age or sports level.